Studies in symbolic interaction. Vol. 33 - Denzin, Norman K. (Bingley, UK : Emerald, 2009)
Part one of volume 33 of "Studies on Symbolic Interaction" contains seven outstanding contributions by leading symbolic interactionists in the 'Annual Blue Ribbon Papers Series' under the editorial leadership of Lonnie Athens. Part two, under the special issue editorship of Richard King, examines commodity racism: representation, racialization and resistance. Part three presents papers in the 'Annual Peter M. Hall Lecture Series' and Part four presents new interpretive works in the interactionist tradition. International in scope, the series draws upon the work of urban ethnographers, interpretive, constructionist, ethnomethodological, critical race, postcolonial, feminist, queer, and cultural studies traditions. The emphasis is on new thought and research. Essays which interrogate the intersections between biography, media, history, politics and culture are encouraged.
Includes bibliographical references.
Description based on print version record.
Keywords: Social psychology; Symbolic interactionism; Social, group or collective psychology; Social interaction; Psychology -- Social Psychology